2002
DOI: 10.1080/095466302317584430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a single 400 mg dose versus a 7-day 200 mg daily dose of itraconazole in the treatment of tinea versicolor

Abstract: On the basis of these findings, a single dose of itraconazole 400 mg/day was as effective as the 7-day 200 mg daily dose in the treatment of pityriasis versicolor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Itraconazole, a triazole antifungal, alters fungal cell function similarly to ketoconazole, through inhibition of cytochrome P450-dependent ergosterol synthesis [ 28 ]. To effectively treat PV, a minimum total amount of 1000 mg itraconazole over the course of treatment was required to produce a significant mycological response [ 51 ]. Treatment once daily for 5 days with 200 mg itraconazole shows high efficacy up to one month following treatment [ 47 , 50 ] and is recommended for treatment of PV [ 62 ].…”
Section: Oral Treatment For Pityriasis Versicolormentioning
confidence: 99%
See 1 more Smart Citation
“…Itraconazole, a triazole antifungal, alters fungal cell function similarly to ketoconazole, through inhibition of cytochrome P450-dependent ergosterol synthesis [ 28 ]. To effectively treat PV, a minimum total amount of 1000 mg itraconazole over the course of treatment was required to produce a significant mycological response [ 51 ]. Treatment once daily for 5 days with 200 mg itraconazole shows high efficacy up to one month following treatment [ 47 , 50 ] and is recommended for treatment of PV [ 62 ].…”
Section: Oral Treatment For Pityriasis Versicolormentioning
confidence: 99%
“…Studies have evaluated the efficacy of 400 mg itraconazole administered once and for 3 days as compared to 200 mg itraconazole for 5 or 7 days [ 50 , 51 ]. While Kose et al (2002) demonstrated that a single 400 mg dose was equivalent to 200 mg for 7 days [ 51 ], Kokturk et al (2002) found a single 400 mg dose to be ineffective, with itraconazole regimens of 400 mg for 3 days and 200 mg for 5 days both producing significantly greater mycological and complete cure ( p = 0.001) [ 50 ]. Although a regimen of 400 mg itraconazole for 3 days may be an alternative to 200 mg itraconazole for 5 days, there is not enough evidence at this time to warrant changing recommendations from 5 day treatment.…”
Section: Oral Treatment For Pityriasis Versicolormentioning
confidence: 99%
“…Multiple randomized trials have reported 70-100 % mycologic cure with 200 mg itraconazole daily for 7 days [39]. In a randomized, open-label trial, a single 400-mg dose of itraconazole was as effective as 200 mg daily for 7 days [47]. The evidence is also strong for 300 mg fluconazole weekly for up to 2 weeks, which resulted in mycologic cure for 87 % of patients [48].…”
Section: Tinea (''Pityriasis'') Versicolormentioning
confidence: 95%
“…İtrakonazol pitriazis versikolor tedavisinde yüksek etkinlik gösterir. Köse ve ark, erişkinlerde bir günlük 400 mg itrakonazol dozunu, 7 günlük 200 mg/gün itrakonazole etkinlik ve güvenilirlik açısından eşit bulmuşlardır 45 . Çocuklar için önerilen itrakonazol dozu < 50 kg çocuklarda 1 haftalık tek kür 5mg/kg/gün, ≥ 50 kg çocuklarda 200 mg/gün önerilir 20 .…”
Section: Tedaviunclassified